The associations of early specialisation and sport volume with musculoskeletal injury in New Zealand children - McGowan, J.; Whatman, C.; Walters, S. (Journal of Science and Medicine in Sport, 2020)
Objective To investigate associations of early specialisation (highly specialised before age 13 years) and sport participation volume with injury history in New Zealand children.